PENGARUH PENGGUNAAN INTERNET TERHADAP KESADARAN POLITIK (KASUS PILKADES 2019 DI DESA CICADAS, KACAMATAN GUNUNGPUTRI, KABUPATEN BOGOR) - Muhamad Syaipuloh; Roni Jayawinangun; Yogaprasta Adi Nugraha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
This research was conducted to analyze about the effect of internet use on political awareness. This study uses one independent variable, namely internet use and one dependent variable, political awareness. The sampling technique used was Non-probability sampling with accidental sampling technique. The data analysis method used is a quantitative analysis of the validity and reliability test, the classic assumption test, simple linear regression analysis, T test and F test and the coefficient of determination using SPPS software version 22 for windows. The results showed the points of the indicator variables X are intensity, usefulness, effectiveness and variable Y which consists of indicators of knowledge, understanding, attitudes, and patterns of behavior (actions) the results are valid and reliable. In the classical assumption test data is normally distributed, heteroscedasticity symptoms occur. In the hypothesis test the use of the internet has a not positive and not significant influence on political awareness.